(untitled) (Journal of the Sylhet Agricultural University, 2025)
Cauliflower (Brassica oleracea var. botrytis L.) and cabbage (Brassica oleracea var. capitata L.) are important winter vegetable crops cultivated in Bangladesh. Planting date is crucial for successful production, but the farmers of the haor areas generally cultivate cauliflower and cabbage not maintaining proper planting dates. The study aimed to search the suitable varieties and planting dates of cauliflower and cabbage. Two individual experiments were conducted in Naogaon village at Dekar haor in Sunamganj district from October 2018 to February 2019. Three planting dates- 5 November, 15 November and 25 November were selected for both the experiments. In experiment one, two hybrid cauliflower varieties- Shira Giko, White Mountain and one OP variety Queen were selected. Atlas 70 and Queen F1 were included in experiment two. The experiments followed two factors randomized complete block design (RCBD) with three farmers’ replications. Data were collected on curd diameter, curd yield, gross and marketable yield for cauliflower. The cabbage head diameter, head yield, gross and marketable yield data were also recorded. Economic performance was calculated for the cost of production, ross return, net return and BCR for both the crops. The result showed that the curd diameter (37.56 cm), curd yield (16.36 t ha-1), marketable yield (25.83 t ha-1), gross yield (50.48 t ha-1), and BCR (4.55) were highest on 15th November in the case of cauliflower. Again, head diameter (56.6 cm), head yield (49.17 t ha-1), marketable yield (61.31 t ha-1), gross yield (75.91 t ha-1), and BCR (6.28) were highest on 5th November for cabbage. Cauliflower variety, Shira Giko and cabbage variety, Atlas 70, were the high-yielding varieties compared to others. Mid- November and early November planting were suitable for cauliflower and cabbage cultivation, respectively in the haor areas. J. Sylhet Agril. Univ. 12(1): 84-93, 2025